Pathological analysis of type 2 diabetes mellitus patients of different ages accompanying renal disease - YANG Hong-xia; LI Xiao-li; ZHU Ji-li; DING Guo-hua (Linchuang shenzangbing zazhi)
Objective To analyze the pathological features of renal disease in type 2 diabetes mellitus(T2 DM)patients of different ages,further to explore their predictive value and to clarify the importance of renal biopsy.Methods T2 DM patients who received renal biopsy from2008 to 2017 were recruited in this study.Pathological data were retrospectively collected.According to the pathological findings,135 patients were fallen into non-elderly group(<60 years old with the age range of 17 to59 and the average age of 45.8±9.8 years old)and43 into older age group(≥60 years old with the age range of 60 to 73 and the average age of 64.7±4.1 years old).Three subgroups were created:diabetic nephropathy(DN),non diabetic renal disease(NDRD)and DN+NDRD.Results(1)In non-elderly group,there were 63 patients in DN subgroup(46.67%),33 in NDRD subgroup(24.44%)and 39 in DN+NDRD subgroup(28.89%);In older age group,there were 17 patients in DN subgroup(39.53%),13 inNDRD subgroup(30.23%)and 13 in DN+NDRD subgroup(30.23%).(2)102 patients in non-elderly group were complicated with DN(75.56%),and 30 patients in older age group were complicated with DN(69.76%).No significant difference existed between the two groups(P>0.05).(3)72 patients in non-elderly group were complicated with NDRD(53.33%),and 26 patients in older age group were complicated with NDRD(60.47%).No significant difference existed between the two groups(P>0.05).(4)NDRD was distributed throughout all types of nephropathy.IgA nephropathy(IgAN)(36.11%)was dominated in non-elderly group,and membranous nephropathy(MN)(42.31%)was the most common finding in older age group.No significant difference existed in the occurrence of IgAN between the two groups(P>0.05).The occurrence of MN in older age group was significantly higher than in non-elderly group(P<0.05).(5)Lupus nephritis(LN),hepatitis B virus associated glomerulonephritis(HBV-GN)and focal segmental glomerulosclerosis(FSGS)were more seen in non-elderly group.(6)The incidence of minimal change disease(MCD),mesangial proliferative glomerulonephritis(MPGN),glomerular minor lesion and Henoch-Schonlein purpura nephritis(HSPN)showed no significant difference between the two groups(P>0.05).Conclusions Only renal pathology can diagnose the types of nephropathy in patients with T2 DM of different ages,and it is of great value to guide future clinical practice to expand the scope of renal biopsy,improve the rate of renal biopsy,which will improve the prognosis of patients through early diagnosis and early treatment.